The Effect of the Talaqqi Method on the Ability to Read Short Surahs Among Early Childhood Children - Oriana Fitria; Diana Silviani; Eko Rojana; Safriadi Safriadi (Ahlussunnah: Journal of Islamic Education, 2026)
Islamic religious education in early childhood plays a crucial role in establishing the foundations of faith, moral values, and a love for the Quran. However, the ability to read short surahs among children aged 5–6 years remains relatively low, particularly in mastering hijaiyah letters, applying tajweed rules, and distinguishing between long and short pronunciations. This study aims to examine the effect of the talaqqi method on the ability to read short surahs in early childhood. This study employed a quantitative approach with a quasi-experimental design involving an experimental group and a control group. The sample consisted of 30 children selected through purposive sampling. Data were collected using a test of short surah reading ability and analyzed using descriptive and inferential statistics, including tests of normality, homogeneity, and an independent samples t-test. The results showed that the mean score of reading ability in the experimental group (M = 80.93) was higher than that of the control group (M = 73.67). The hypothesis testing indicated that the calculated t-value (2.175) was greater than the critical t-value (2.160) at a significance level of 0.05, indicating a statistically significant effect of the talaqqi method on reading ability. These findings suggest that the talaqqi method is effective in improving Quranic reading skills in early childhood.